The Importance Of Digital Technologies In The Creative Thinking Process Of Students’ In Higher Education (Zien Journal of Social Sciences and Humanities, 2026)
This paper substantiates the didactic and psychological importance of digital technologies for fostering university students’ creative thinking. The study aims to conceptually explain how digital learning environments, data-informed analytics, and collaborative platforms influence key stages of the creative process: problem reframing, idea generation, prototyping, and reflection. The methodology combines a systematic literature review, conceptual synthesis, instructional design principles, and an evaluation logic grounded in digital trace data. The scientific novelty lies in framing digital technologies not merely as instructional tools but as enabling conditions that elicit creative cognition, and in proposing an integrative didactic framework linking creativity indicators to measurable patterns of digital learning activity. The findings highlight that adaptive content delivery, rapid feedback cycles, and networked co-creation are central mechanisms through which higher education can develop students’ creative competencies while maintaining transparency and assessability of learning outcomes